Single-cell light-sheet fluorescence 3D images of tumour-stroma spheroid multicultures - Akos Diosdi; Filippo Piccinini; Timea Boroczky; Gabriella Dobra; Gastone Castellani; Krisztina Buzas; Peter Horvath; Maria Harmati (Scientific Data)
Abstract Spheroids are widely used in oncology for testing drugs, but models composed of a single cell line do not fully capture the complexity of the in vivo tumours targeted by chemotherapy. Developing 3D in vitro models that better mimic tumour architecture is a crucial step for the scientific community. To enable more reliable drug testing, we generated multiculture spheroids and analysed cell morphology and distribution over time. This dataset is the first publicly available single-cell light-sheet fluorescence microscopy image collection of 3D multiculture tumour models comprising of three different cell lines analysed at different time points. Specifically, we created models composed of one cancer cell line (melanoma, breast cancer, or osteosarcoma) alongside two stromal cell lines (fibroblasts and endothelial cells). Then, we acquired single-cell resolution light-sheet fluorescence 3D images of the spheroids to analyse spheroid morphology after 24, 48, and 96 hours. The image collection, whole spheroid annotations, and extracted features are publicly available for further research and can support the development of automated analysis models.